2009
DOI: 10.1007/s00127-009-0023-7
|View full text |Cite
|
Sign up to set email alerts
|

Secondary prevention of hazardous alcohol consumption in psychiatric out-patients: a randomised controlled study

Abstract: Brief intervention seems to be effective to reduce hazardous alcohol consumption in psychiatric outpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 29 publications
2
42
1
3
Order By: Relevance
“…As the screening instrument applies different cut off's for men and women, the missing sex did not allow us to analyze these results, 29 patients who left more than three questions unanswered were also excluded. When 1-3 questions were not completed (n ¼ 14, AUDIT) missing data were imputed with the mean for this question in the corresponding subgroup for sex and age, as was performed in intervention article from this sample (Eberhard et al, 2009). Another 130 patients misunderstood the questionnaire concerning drug-habits (and reported prescribed tranquilizers), their DUDIT scores were excluded from the analyses.…”
Section: Patientsmentioning
confidence: 99%
“…As the screening instrument applies different cut off's for men and women, the missing sex did not allow us to analyze these results, 29 patients who left more than three questions unanswered were also excluded. When 1-3 questions were not completed (n ¼ 14, AUDIT) missing data were imputed with the mean for this question in the corresponding subgroup for sex and age, as was performed in intervention article from this sample (Eberhard et al, 2009). Another 130 patients misunderstood the questionnaire concerning drug-habits (and reported prescribed tranquilizers), their DUDIT scores were excluded from the analyses.…”
Section: Patientsmentioning
confidence: 99%
“…Respecto de diferencias de género, nuestros resultados son coherentes con varios informes y encuestas epidemiológicas publicadas que describen tasas más altas de TUA en hombres que en mujeres, tanto para la población general Hasin et al, 2007;Keyes et al, 2008;Khan et al, 2013;Rehm et al, 2015) como para pacientes psiquiátricos (Cantor-Graae et al, 2001;Dervaux et al, 2006;Eberhard et al, 2009;McCreadie, 2002;Satre et al, ADICCIONES, 2017 · VOL. xx NÚM.…”
Section: Discussionunclassified
“…Varios autores han descrito diferencias en la prevalencia de TUA según género en las poblaciones general y psiquiátrica (Cantor-Graae et al, 2001;Dervaux et al, 2006;Eberhard, Nordström, Höglund, y Ojehagen, 2009;Goldstein, Smith, Dawson, y Grant, 2015;Gual et al, 2016;Hasin, Stinson, Ogburn, y Grant, 2007;Keyes, Grant, y Hasin, 2008;Khan et al, 2013;McCreadie, 2002;Pulido et al, 2014;Rehm et al, 2015;Satre, Wolfe, Eisendrath, y Weisner, 2008). También se ha relacionado la frecuencia de TUA con la edad (Hasin et al, 2007), especialmente con pacientes psiquiátricos (Sheidow, McCart, Zajac, y Davis, 2012).…”
unclassified
“…Although very limited in number and methodological quality, there is some evidence on brief intervention for heavy drinkings such as psychiatric outpatient setting, [45] community-based counselling centres, sexual health clinics, and antenatal care and postpartum care settings [46][47][48][49]. However, none of the studies reported a superior benefit for brief intervention as compared to routine care [50,51].…”
Section: Alcohol Brief Interventions In Miscellaneous Settingsmentioning
confidence: 99%